Deliberations about a perfect storm – The meaning of justice for food energy water-nexus (FEW-Nexus). (15th August 2018) - Schlör, Holger; Venghaus, Sandra; Fischer, Wiltrud; Märker, Carolin; Hake, Jürgen-Friedrich
Abstract: The current global developments have the potential to cause a 'perfect storm' at the core of the Anthropocene: the Food-Energy-Water-Nexus. To discuss the ethical consequences of these developments, i.e., insufficient access to the life sustaining nexus resources, the analysis is focused on Rawls' theory of justice and its implementation in Germany with a special focus on the FEW nexus. Rawls stresses in his theory of justice the prominent meaning of institutions for a fair society to meet societal challenges and to meet the challenge of our time: a stable and just society. Hence, the realization of his ideas in Germany is scrutinized and income tax and value added tax are interpreted in the sense of Douglas North and John Rawls as institutions and formal rules of society. This paper focuses on taxes as the most important institutional incentive to organize and structure the political, social and economic cooperation and analyses how these incentives affect selected German households (all households, singles, single man and woman, and couples) with respect to income and FEW expenditures. The relevant income and usage data sample (Einkommens- und Verbrauchsstichprobe (EVS)) for Germany is used for the analysis of the distribution of income types, FEW expenditures and the revenues of income tax and value added tax, i.e., the main instruments to manage the challenges of the FEW nexus. Therefore two distribution measures have been used: the dispersion of income, taxes and FEW expenditures and their skewness. Five household groups were selected for this analysis: All households, all single households, the single women households, the single men households, as well as the households of couples. The EVS data sample allows the analysis of consequences of the current societal conditions on the various households and thus serves to provide a deeper understanding of the differences between singles and couples but also between single women and men. Graphical abstract: Image 1 Highlights: Focus on the influence of Rawls' theory of justice in Germany and its FEW nexus. Income tax and value added tax are interpreted as institutional rules of society. How these institutions affect the income and expenditures of German households.